3d−4d hybridization anomaly in NixPd1−x alloys at quantum critical point. (July 2017) - Swain, P.; Srivastava, Sanjeev K.; Srivastava, Suneel K.
Abstract: First-principles density functional theory computations of electronic structure and local magnetic properties of the non-fluctuating ground state of Ni x Pd 1 − x alloy system around its quantum critical point x c =0.026 have been performed. The density of states at the Fermi energy and certain other parameters characterizing the Ni 3 d − Pd 4 d hybridization apparently follow power-laws with x similar to that obeyed by the reported ferromagnetic to paramagnetic transition temperature. The width of Pd 4 d density of states (DOS) and centroid of Ni 3 d DOS show peak-like anomalies in the neighbourhood of x c, and so indicate a possible scenario of the existence of a definite relation between the orbital hybridization and the emergence of quantum fluctuations in the system. Highlights: Zero-K properties of Ni x Pd 1 − x alloys near quantum critical point are calculated. Ni 3 d - Pd 4 d orbital hybridization is semi-quantitatively derived from partial densities of states. The hybridization exhibits an anomaly near the quantum critical point. The study reveals a possible relation between hybridization and quantum fluctuations.